Human platelet antigen genotyping of platelet donors in southern Brazil. (24th July 2015) - Merzoni, J.; Fagundes, I. S.; Lunardi, L. W.; Lindenau, J. D.‐R.; Gil, B. C.; Jobim, M.; Dias, V. G.; Merzoni, L.; Sekine, L.; Onsten, T. G. H.; Jobim, L. F.
Summary Human platelet antigens (HPA) are immunogenic structures that result from single nucleotide polymorphisms (SNPs) leading to single amino acid substitutions. This study sought to determine the allele and genotype frequencies of HPA‐1, HPA‐2, HPA‐3, HPA‐4, HPA‐5 and HPA‐15 in platelet donors from the state of Rio Grande do Sul (RS), Brazil, and compare their allele frequencies to those observed in other populations. HPA genotyping was performed by PCR‐SSP method. The study sample comprised 201 platelet donors (167 Caucasians and 34 non‐Caucasians). Allele 'a' was that most commonly found for HPA‐1 to 5 in both groups. The HPA‐15ab genotype predominated over homozygous genotypes of this system. Fisher's exact test revealed statistically significant differences for the HPA‐5 system, with a greater prevalence of the HPA‐5b allele in non‐Caucasians. The neighbour‐joining method and principal components analysis revealed genetic proximity between our Caucasian group and European populations. We conclude that the allele frequencies of HPA‐1 to 5 and HPA‐15 found in our Caucasian sample are similar to those reported for European populations. These findings corroborate the ethnic makeup of the population of RS. The higher frequency of the HPA‐5b allele found in the non‐Caucasian group of our sample suggests the possibility of allosensitization in patients who receive platelet transfusions from genetically incompatible donors.